If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3y + 2) = -2 Reorder the terms: 7(2 + 3y) = -2 (2 * 7 + 3y * 7) = -2 (14 + 21y) = -2 Solving 14 + 21y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 21y = -2 + -14 Combine like terms: 14 + -14 = 0 0 + 21y = -2 + -14 21y = -2 + -14 Combine like terms: -2 + -14 = -16 21y = -16 Divide each side by '21'. y = -0.7619047619 Simplifying y = -0.7619047619
| -12=-x+3x | | 8(5x+10)=40x-5 | | 24+8(c-3)=7c+5 | | 0.02x-0.2=4 | | 5(1+36)=-43+9b | | xy-3x-y=3 | | 5(x+6)=4(3-2x) | | f(x)=2x^2+11x | | 3=g | | 11x+6=11x-1 | | 5x+9=-17 | | x+2x-13=2 | | -7q+-14=-84 | | 8b-9=3/4(8b-12) | | 4x-1=2(x-3)+1 | | 2x-4(x-3)=-2+3x-16 | | 5x+6=-45-3x | | 3x+14=28 | | 4*k+m*n=n-3 | | 4x-2x+5=11 | | -3.7= | | 2x-4(x-5)=-2+3x-16 | | (-4)-6=-34 | | 7y-3(y-4)=10 | | 4(3x-7)=-2x | | 4(3x-7)=-2 | | 5x-1-ln(5)=0 | | 4b+-6=-14 | | -3x+5y=-4.5 | | 6(5-3x)=7(10-2x) | | 5(3y+3)-18=17+5y | | -4-6=-34 |